2003
DOI: 10.1152/japplphysiol.00248.2002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cardiac hypertrophy and heart failure due to volume overload in the rat

Abstract: Alterations in general characteristics and morphology of the heart, as well as changes in hemodynamics, myosin heavy chain isoforms, and beta-adrenoceptor responsiveness, were determined in Sprague-Dawley rats at 1, 2, 4, 8, and 16 wk after aortocaval fistula (shunt) was induced by the needle technique. Three stages of cardiac hypertrophy due to volume overload were recognized during the 16-wk period. Developing hypertrophy occurred within the first 2 wk after aortocaval shunt was induced and was characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
116
2
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(135 citation statements)
references
References 46 publications
15
116
2
2
Order By: Relevance
“…It was reported that the slope of the V O 2 -PVA relation was related to the ratio of the myosin isoform component from predominantly V3 to predominantly V1 (i.e., the slope of the V O 2 -PVA relation increases when the V1-to-V3 ratio increases, and the slope of the V O 2 -PVA relation is unchanged when the V1-to-V3 ratio decreases) (6). It was also reported that a progressive decrease in V1 and an increase in V3 were apparent in the LV 8-to 16 wk after AV shunt (21). This report is consistent with the almost unchanged slope of the V O 2 -PVA relation in the VO rats.…”
Section: Chemomechanical Energy Transductionmentioning
confidence: 95%
“…It was reported that the slope of the V O 2 -PVA relation was related to the ratio of the myosin isoform component from predominantly V3 to predominantly V1 (i.e., the slope of the V O 2 -PVA relation increases when the V1-to-V3 ratio increases, and the slope of the V O 2 -PVA relation is unchanged when the V1-to-V3 ratio decreases) (6). It was also reported that a progressive decrease in V1 and an increase in V3 were apparent in the LV 8-to 16 wk after AV shunt (21). This report is consistent with the almost unchanged slope of the V O 2 -PVA relation in the VO rats.…”
Section: Chemomechanical Energy Transductionmentioning
confidence: 95%
“…In rats, significant cardiac hypertrophy develops 4 weeks after shunt induction, with compromised LV contractility and increased end-diastolic pressure [256]. Severe volume overload from a large aortocaval fistula initially leads to depressed LV function followed by a compensatory hypertrophy and near normal function at 4 weeks [165,307]. Decompensated hypertrophy or CHF develops between 8 and 16 weeks after the intervention and is characterized by a decline in systolic and diastolic function [34,308] and a shift between myosin heavy chain isoforms expression [307].…”
Section: Volume-overload-induced Hfmentioning
confidence: 99%
“…Severe volume overload from a large aortocaval fistula initially leads to depressed LV function followed by a compensatory hypertrophy and near normal function at 4 weeks [165,307]. Decompensated hypertrophy or CHF develops between 8 and 16 weeks after the intervention and is characterized by a decline in systolic and diastolic function [34,308] and a shift between myosin heavy chain isoforms expression [307]. Nonetheless, shunt closure has been reported in 7% of the cases, which means that it is necessary to confirm the patency of the shunt at the end of investigation.…”
Section: Volume-overload-induced Hfmentioning
confidence: 99%
“…Therefore, it is important to determine the mechanism responsible for volume overloadinduced ventricular remodeling. In this study, we created a volume overload rat model by abdominal artery-inferior vena cava puncture [25] . The Qp/Qs ratios in the remaining shunt rats were close to 2.0, suggesting successful creation of shunts and sustained volume overload.…”
Section: Discussionmentioning
confidence: 99%